107k views
1 vote
How to solve this equation showing step by step. 3(t - 1) = 9 + t

User Yeon
by
7.6k points

2 Answers

4 votes
3(t-1)=9+t
3t-3=9+t
3t-t=3+9
2t=12 (divide both sides by 2)
t=6
User Miguel Durazo
by
6.7k points
3 votes
1st: Expand the bracket
3t-3=9+t
2nd: Add the 3 to get rid of it on the first side. Do this to both sides
3t=12+t
3rd: Take away the t on the left hand side and one on the right hand side to just be left with t's on one side and integers on the other side
2t=12
4th: Divide both sides by 2 to find 1t
t=6

Hope this helps!! :)

User Virgil Dupras
by
7.0k points